Rosai‐dorfman disease with extranodal involvement. (29th July 2013) - Hashimoto, Kaori; Kariya, Shin; Onoda, Tomoo; Ooue, Tetsuo; Yamashita, Yasuhiko; Naka, Kikuko; Okano, Mitsuhiro; Nishizaki, Kazunori
<x xml:space="preserve">Abstract</x> Rosai‐Dorfman disease is a rare condition of marrow hematopoietic stem‐cell origin. Patients can show extranodal involvement as well as lymphatic involvement, but only about 5% of extranodal cases involve intracranial lesions. A 53‐year‐old male was admitted to our hospital with bilateral cervical lymphadenopathy. Intracranial tumors and bone lesions were also detected. Cervical lymph node biopsy and intracranial tumor resection were performed, and histopathological examination revealed Rosai‐Dorfman disease. The patient showed good clinical course without significant enlargement of the tumor. This study describes the case of a patient with Rosai‐Dorfman disease presenting with massive cervical lymphadenopathy mimicking malignant neoplasm. Laryngoscope, 124:701–704, 2014